2017
DOI: 10.1007/s40119-017-0091-9
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes in Cardiovascular Medicine

Abstract: Exosomes are small, extracellular membrane-bound particles that mediate intercellular transport of a cytosolic cargo. Exosomal transfer of micro-RNA can modify gene expression in targeted cells. Exosome-based endocrine/paracrine signaling has been shown to be involved in a wide range of physiological processes including those associated with cardiovascular injury and disease, but remains relatively poorly understood. Exosomes offer great potential to the clinical field, with applications in both diagnostics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 101 publications
0
24
0
Order By: Relevance
“…Currently, it has been recognized that circulating exosomes released from leukocytes, platelets, and endothelial cells, as regulators of CAD, could reflect the stage or progression of the disease [16]. It has also been proved that the changes of exosome contents including lncRNAs may be measured as potential diagnostic and prognostic biomarkers and therapeutic targets for CAD [13,14,17]. erefore, we aimed to determine whether or not certain circulating exosome-encapsulated lncRNAs could be as promising biomarkers for the diagnosis of CAD, especially in an early stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it has been recognized that circulating exosomes released from leukocytes, platelets, and endothelial cells, as regulators of CAD, could reflect the stage or progression of the disease [16]. It has also been proved that the changes of exosome contents including lncRNAs may be measured as potential diagnostic and prognostic biomarkers and therapeutic targets for CAD [13,14,17]. erefore, we aimed to determine whether or not certain circulating exosome-encapsulated lncRNAs could be as promising biomarkers for the diagnosis of CAD, especially in an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the changes of exosome contents including lncRNAs can lead to significant alterations in certain biological processes, which may play important roles in the development and progression of CAD. Furthermore, exosome contents also can be measured as potential diagnostic and prognostic biomarkers and therapeutic targets for CAD [13,14]. It was reported that exosomal lncRNA GAS5 could regulate the apoptosis of macrophages and vascular endothelial cells in atherosclerosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Research on CVD with some exosome cargos (miRNAs, lipids, and proteins) provide the development of noninvasive discovery of novel biomarkers. 299,300,302,303 However, their clinical use remains juvenile. A study, utilizing genetically modified mice, shows the critical requirement for miRNAs in cardiac development, as mice deficient in Dicer experience cardiac failure.…”
Section: Micrornas and Exosomal Mirnas Are Gene Regulators And Emergimentioning
confidence: 99%
“…306 Furthermore, treatment of miR-133a inhibitors reduces the level of cardiac hypertrophy. 306 The levels of miR-22, 99a, 214, and 21 increased expression or decreased expression of miR-15, 320, 132, 212, 652, 92a, and 34, which provides beneficial or protective effects in the treatment of CVD 299,302,303 (Fig. 8).…”
Section: Micrornas and Exosomal Mirnas Are Gene Regulators And Emergimentioning
confidence: 99%
“…Exosomes are critical cellular communicators between cells, which offer the clinical potential for both detection and treatment of various diseases. Noteworthy, exosomes are of great increasing interest for three major reasons with potential clinical applications in CVDs as following: (1) diagnostics and prognostic biomarkers, (2) therapeutic strategies, and (3) drug carriers (Dykes, 2017 ; Zhang et al, 2017 ).…”
Section: Potential Application Of Exosomesmentioning
confidence: 99%